Manfaat Usahatani Jagung Varietas Bisi-228 Terhadap Tingkat Kesejahteraan Rumah Tangga Petani di Kecamatan Watopute Kabupaten Muna - Samsul Alam Fyka; Sri Yuni Rahmawati (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
The purpose of this study was to determine the benefits of corn farming of Bisi-228 variety on the level of welfare. This research was conducted in Wakadia Village, Watopute District, Muna Regency. The population of this study were all corn farmers of Bisi-2 variety as many as 236 people. While the number of samples was determined by purposive sampling method so that the number of samples in this study were 35 people. The data analysis used is welfare analysis through the UMP approach and benefit cost ratio (BCR). The result of this research is that maize farming with Bisi-228 variety is able to provide greater income than maize farming in other areas, which is IDR. 19,047,324/MT or IDR. 3,174,554/month and farming is also able to be profitable for farmers and is feasible to be developed because of the BCR value. the amount is Rp. 4.83. Bisi-228 maize farming also provides benefits for the welfare of farmers, as many as 19 people or 54% are classified as prosperous with a monthly income greater than the Southeast Sulawesi UMP while the remaining 16 people or 46% are categorized as not prosperous because the amount of income earned is below the Sulawesi UMP. Southeast.